2012
DOI: 10.1101/gad.178491.111
|View full text |Cite
|
Sign up to set email alerts
|

Rif1 is a global regulator of timing of replication origin firing in fission yeast

Abstract: One of the long-standing questions in eukaryotic DNA replication is the mechanisms that determine where and when a particular segment of the genome is replicated. Cdc7/Hsk1 is a conserved kinase required for initiation of DNA replication and may affect the site selection and timing of origin firing. We identified rif1D, a null mutant of rif1 + , a conserved telomere-binding factor, as an efficient bypass mutant of fission yeast hsk1. Extensive deregulation of dormant origins over a wide range of the chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
307
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 238 publications
(336 citation statements)
references
References 49 publications
20
307
4
3
Order By: Relevance
“…Here we demonstrated that budding yeast Rif1 is involved in regulating DNA replication genome-wide, consistent with findings in fission yeast and mammalian cells and suggesting that DNA replication control by Rif1 is conserved through eukaryotes (Cornacchia et al 2012;Hayano et al 2012;Yamazaki et al 2012). Rif1 restrains replication by counteracting the action of DDK, and loss of Rif1 partially compensates for impaired DDK function in a cdc7-1 mutant strain.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Here we demonstrated that budding yeast Rif1 is involved in regulating DNA replication genome-wide, consistent with findings in fission yeast and mammalian cells and suggesting that DNA replication control by Rif1 is conserved through eukaryotes (Cornacchia et al 2012;Hayano et al 2012;Yamazaki et al 2012). Rif1 restrains replication by counteracting the action of DDK, and loss of Rif1 partially compensates for impaired DDK function in a cdc7-1 mutant strain.…”
Section: Discussionsupporting
confidence: 68%
“…Previous investigations showed that deleting S. pombe rif1 + suppresses mutations in DDK and that S. pombe and mammalian Rif1 affect genome-wide replication timing (Cornacchia et al 2012;Hayano et al 2012;Yamazaki et al 2012). A previous study of the S. cerevisiae rif1D replication program showed a shortened interval between replication of early and late sequences, with telomeric origins in particular replicating aberrantly early (Lian et al 2011).…”
Section: Backup S-phase Controls and Regulation Of Replication Timingmentioning
confidence: 99%
See 3 more Smart Citations